Effect of idealised influence, inspirational motivation, intellectual stimulation and individualised consideration on service sector employees’ performance in Karachi, Pakistan - Haseeb, Abdul; Suppramaniam, Subaashnii; Subramaniam, Anusuiya (Macrothink Institute, 2021)
Transformational leaders motivate their employees in such a way that employees start adopting the vision of the organisation as their own vision. Precisely research concerning relationship between transformational leadership and employee’s performance has been conducted by many researchers as well as in leading sectors and industries of Pakistan. However, there is a dearth of researches that investigates the effect of four dimensions of transformational leadership on employee’s performance in services sector. Therefore, this study was carried out to assess the relationship between transformational leadership and its four dimensions on the performance of employees considering services sector in Karachi, Pakistan. Snowball sampling was utilised and participants were selected among the service sector employees in Karachi, Pakistan. Hypotheses were tested by utilising Smart-PLS. The findings revealed that individualised consideration and idealised influence significantly contributes towards enhanced performance of employees. Contrary to expectation, intellectual stimulation and inspirational motivation was found to be not significant with employee performances’. It is suggested that management of service sector organisations’ should acknowledge the importance of the dimensions of transformational leadership on employees’ performance, which will eventually will lead to the achievement of the strategic goals and tasks defined by the service sector organisation.